2017
DOI: 10.1248/bpb.b16-00364
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Suppresses Epithelial–Mesenchymal Transition of Renal Tubular Epithelial Cells through the Inhibition of Akt/mTOR Pathway

Abstract: Curcumin has exhibited a protective effect against development of renal fibrosis in animal models, however, its underlying molecular mechanisms are largely unclear. Therefore, we investigated the anti-fibrosis effects of curcumin in transforming growth factor-β1 (TGF-β1)-induced epithelial-to-mesenchymal transition (EMT), and the mechanism by which it mediates the phosphatidylinositol 3-kinase (PI3K)/Akt pathway. Human kidney tubular epithelial cells (HKCs) were treated with TGF-β1 or curcumin alone, or TGF-β1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 40 publications
2
28
0
Order By: Relevance
“…Considering curcumin as a potential anti-ageing factor it is important to mention that it could act not only by mimicking of DR and exercise but is also able to inhibit the Akt/mTOR signaling pathway (Zhu et al 2016; Guo et al 2016; Jiao et al 2016; Sikora et al 2010a). …”
Section: Introductionmentioning
confidence: 99%
“…Considering curcumin as a potential anti-ageing factor it is important to mention that it could act not only by mimicking of DR and exercise but is also able to inhibit the Akt/mTOR signaling pathway (Zhu et al 2016; Guo et al 2016; Jiao et al 2016; Sikora et al 2010a). …”
Section: Introductionmentioning
confidence: 99%
“…Wnt/β‐catenin and PI3K/AKT signaling pathways play important roles in the regulation of EMT, and we predicted that Mn12Ac might inhibit the EMT of breast cancer cells through regulating these two pathways. Using western blotting assay, we found that Mn12Ac significantly reduced the expressions of Wnt1 and β‐catenin (Fig a).…”
Section: Resultsmentioning
confidence: 99%
“…Curcumin's mediation of the AKT signaling pathways plays protective roles in multiple organs and with ischemia‐reperfusion injury. Zhu et al () study demonstrated that curcumin suppresses the epithelial‐mesenchymal transition of renal tubular epithelial cells through inhibition of the Akt/mTOR pathway. Thus, we asked whether the APPL1/Akt signaling pathway mediated the pathogenesis of IR‐induced latefibrosis in vitro.…”
Section: Discussionmentioning
confidence: 99%